Surgical Treatment - Tihanyi, Tibor F; Pulay, István; Winternitz, Tamás; Flautner, Lajos (JOP. Journal of the Pancreas)
Pancreatic carcinoma is a devastating disease. Untreated 5-year survival is 0%. The only possibility of being cured is given by surgical removal of the tumor. Pancreatoduodenectomy previously involved high morbidity and mortality rates until it was postulated that palliation gave better results. Today, morbidity and mortality rates have been decreased to an acceptable level, mortality rates in specialized centers being under 5%. Prognostic factors determining survival were found to be the size of the tumor, grade, lymph node involvement and stage. In order to be able to compare results of the different centers, standardization of the surgical technique is mandatory. It is unanimously accepted that in order to improve survival in pancreatic carcinoma, the radicality of the surgical procedure should be increased to include lymphadenectomy. Postoperative adjuvant therapy could also be a determinant factor. Prospective randomized clinical trials will give an answer to these still unanswered questions. Image: Semmelweis University logo. Budapest, Hungary.